Green Innovation, Green Dynamic Capability, and Enterprise Performance: Evidence from Heavy Polluting Manufacturing Enterprises in China - Haiyan Li (Complexity)
Green innovation is widely regarded as a beneficial strategy for manufacturing enterprises to accelerate green transformation. Drawing the natural resource-based view with dynamic capabilities, this study proposes a model linking green innovation, green dynamic capability, and firm performance. Using survey data from 236 heavy polluting manufacturing firms in China, this study investigates the impact of green innovation on firm performance. The results show that green innovation is positively correlated with both enterprise performance and green dynamic capability, whereas green dynamic capability also has a significant impact on enterprise performance. Furthermore, the survey found that the green resource integration ability, organizational learning capability, and environmental insight capability of green dynamic capability play a moderating effect on the relationship between green innovation and enterprise performance. Additionally, we provide useful enlightenment for policymakers and business managers to stimulate green innovation in enterprises. Our research not only assists managers to better grasp the effects of green innovation practices but also provides some important implications for policymakers.